Statistical correlations between cells, blood vessels, oxytalan fibres and nerves in normal mouse molar periodontal ligament using transmission electron microscopy - Freezer Simon R.; Sims Milton R. (Sciendo, 1998)
Mandibular ligament mesiobuccal to the mouse first molar was sectioned from the alveolar crest to the tooth apex in three animals. At statistically predetermined levels, TEM sections were examined and then quantified using stereological techniques. Statistically significant associations between periodontal cells, blood vessels, oxytalan fibres, nerves and cells were elucidated by constructing Pearson correlation matrices on a Cyber 173 mainframe computer. These results establish a mathematical model for normal mouse molar periodontal ligament. Fibroblasts demonstrate a statistically significant correlation with both oxytalan fibres enclosed in collagen bundles (p < ·01) and oxytalan fibres lying adjacent to periodontal cells (p < ·01). Moreover, K-cells have a statistically significant correlation with perivascular oxytalan fibres (p < ·05), myelinated and unmyelinated axons (p < ·05 and p < ·01, respectively) and anatomically distinct blood vessels which contain 88 percent of the periodontal blood volume (p < ·01). The findings also indicate that separate vascular and nonvascular populations of oxytalan fibres and nerve axons occur within the ligament. A further statistical association exists between myelinated and unmyelinated nerves in both the tissue parenchyma (p < ·01) and within blood vessel walls (p < ·01). These previously unreported associations of complex structures may delineate operant mechanisms that could influence functional tooth support and orthodontic tooth movement.